Wish I was here [videorecording (DVD)] - Braff, Zach, 1975-; Braff, Zach, 1975-; Hudson, Kate, 1979-; Parsons, Jim, 1973-; Avery, James, 1945-2013 ([Publisher not identified], 2014)
Aidan Bloom, a 35-year-old struggling actor, father, and husband, is still trying to find his identity, a purpose for his life. He winds up trying to home school his two children when his father can no longer afford to pay for private education and the only available public school is on its last legs. Through teaching them about life his way, Aidan gradually discovers some of the parts of himself he couldn't find.